Subcontractor Selection Strategy to Minimize Subcontractor Performance Problems Using Analytical Hierarchy Process Method: Case Study at PT. Hutama Karya Infrastruktur - Rohmat Danang Nur Riyadi; A Arviansyah (Quantitative Economics and Management Studies, 2023)
The construction industry shares about 13,4% of the world output in the business field. Subcontractor selection process will have a major effect on the performance results of a construction project. This study will focus on the subcontractor selection strategy to minimize subcontractor performance problems using the Analytical Hierarchy Process (AHP) method assisted by expert choice software in PT. Hutama Karya Infrastruktur. AHP is widely used in construction management research because its permanent ability to deal with many types of decisions. There are five criteria used as research variables, namely price, administration, resources, performance and quality, and partnership strategy. The results showed that price is not the top priority in choosing subcontractors, but the top priorities are performance and Quality, Health, Safety, Security, and Environment (QHSSE). The main sub-criteria on performance and QHSSE are work method and production capacity, this shows that the way of completion or work method and production capacity of equipment or supporting equipment of subcontractors in working on a project were the main priorities.